A tryptophol-containing emulgel ameliorates imiquimod-induced mice psoriasis - Arnon Pudgerd; Kamonwan Jongsomchai; Watcharamat Muangkaew; Laorrat Phuapittayalert; Sataporn Jamsuwan; Teera Chanmanee; Rapeepun Vanichviriyakit; Passanesh Sukphopetch (Scientific Reports)
Abstract Tryptophol (TOH) is an aromatic alcohol, a natural compound, which is produced by various microorganisms. TOH has been reported to have sleep-inducing effects, anti-microbial activities as well as immunoregulatory properties. While TOH was shown to suppress proinflammatory cytokine production in a variety of cell types, in vivo evidence supporting the immunosuppressive effect of TOH remains sparse. Here, we report that TOH reduced the severity of skin inflammation in a mouse model of imiquimod (IMQ)-induced psoriasis. The results revealed that the TOH-containing emulgel decreased the pathological score of the psoriasis area and severity index (PASI). Topical administration of TOH-containing emulgel inhibited keratinocyte proliferation in IMQ-treated skin as indicated by reduced immunoreactivity for Ki67 and decreased mRNA expression of K6, K16 and K17. Skin of TOH-containing emulgel-treated IMQ mice displayed fewer Giemsa-positive cells and CD4+ cells than those of emulgel-treated IMQ mice, suggesting a decreased dermal infiltration of mast cells and CD4+ T cells, respectively. RT-qPCR results showed that interleukin (IL)-17A, IL-23 and IL-33 were downregulated in psoriatic skin of TOH-containing emulgel-treated IMQ mice. Western blot analysis demonstrated that phosphorylation of JAK2 and STAT3, downstream signaling molecules of IL-17A and IL-23, was decreased in TOH-containing emulgel-treated IMQ mice. Additionally, TOH-containing emulgel dermal application alleviated IMQ-induced splenomegaly and suppressed expression of TNFα, IL-1 and IL-6 in spleen and axillary lymph nodes. This study revealed that a TOH-containing emulgel attenuates IMQ-induced inflammation in psoriatic mice and could be a new therapeutic agent for managing psoriasis.